2022
DOI: 10.1002/cmdc.202200234
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Derivatives: Synthesis, Antitumor Activity, and Apoptotic Induction in MCF‐7 Cells via IL‐6/PI3K/Akt/NF‐κB Signaling Pathway

Abstract: Natural products have been widely considered as an important resource for new drugs or lead compounds. Sinomenine (SIN) and its derivatives exert antitumor activity via regulation of inflammatory mediators. For these reasons we synthesized three series of SIN derivatives (compounds 4 a-i, 7 a-c and 11 a-c) as antitumor agents from this natural product. All compounds were prepared by modification at the C1 and C4 positions of the A ring, the C4 position of the A ring, and the C6 and C7 positions of the C ring, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We observed CRC metastasis, considering that IL-6 and IL-10 may increase tumor metastasis by regulating the PI3K/Akt/mTOR signaling pathway. 39,40 The left lobe of the liver of nude mice undergoing liver metastasis was taken uniformly, and the number of liver metastatic foci in each group was counted using a stereoscope. When compared to the model group, the number of metastatic foci was significantly reduced in the CLGH and capecitabine groups.…”
Section: Discussionmentioning
confidence: 99%
“…We observed CRC metastasis, considering that IL-6 and IL-10 may increase tumor metastasis by regulating the PI3K/Akt/mTOR signaling pathway. 39,40 The left lobe of the liver of nude mice undergoing liver metastasis was taken uniformly, and the number of liver metastatic foci in each group was counted using a stereoscope. When compared to the model group, the number of metastatic foci was significantly reduced in the CLGH and capecitabine groups.…”
Section: Discussionmentioning
confidence: 99%
“…7, and HT-29) [68]. In the same year, X. Gao et al found that the SIN derivative 7Cc (11) exhibited anti-breast cancer potency with IC50 values of 1.75 and 0.82 μM against MCF-7 and MDA-MB-231, respectively, and the second-highest cytotoxicity against A549 (IC50 = 1.94 μM).…”
Section: Antitumor Activity Of Sin Derivativesmentioning
confidence: 99%
“…A year later, Q.Z. Hu and others discovered that SIN derivatives 11c (10) displayed pronounced cytotoxicity through the IL-6/PI3K/Akt and NF-κB signaling pathways, with IC 50 values of 3.76-10.26 µM against cancer cells (HeLa, A549, HepG-2, MCF-7, and HT-29) [68]. In the same year, X. Gao et al found that the SIN derivative 7Cc (11) exhibited anti-breast cancer potency with IC 50 values of 1.75 and 0.82 µM against MCF-7 and MDA-MB-231, respectively, and the second-highest cytotoxicity against A549 (IC 50 = 1.94 µM).…”
Section: Anti-inflammatory Activity and Analgesic Activity Of Sinmentioning
confidence: 99%
“…However, sinomenine has the disadvantages of unstable physicochemical properties, poor water solubility, short half-life and low bioavailability, which limits its activity against cancer. Therefore, nanocarriers and molecular modification (such as sinomenine hydrochloride, sinomenine ester derivatives, chlorine-containing derivatives and YL064) is considered an effective method to solve these problems ( 5 ). Sinomenine has been successfully loaded into transmitter to enhance its bioactivity and bioavailability ( 6 ).…”
Section: Introductionmentioning
confidence: 99%